Paxlovid (Nirmatrelvir/Ritonavir)-Induced Tacrolimus Toxicity in Organ Transplant Recipients - A Review on Drug Interactions Involving CYP3A Enzymes - Maideen, Naina Mohamed Pakkir; Al Rashid, Sulthan (Current Drug Safety, 2025)
BackgroundPaxlovid (nirmatrelvir/ritonavir) is the first oral therapy approved by the US FDA to treat patients with mild-to-moderate COVID-19.ObjectiveOur current review focuses on clinical data related to tacrolimus toxicity induced by Paxlovid currently available.MethodsA number of online databases, including LitCovid, Scopus, Web of Science, Embase, EBSCO host, Google Scholar, Science Direct, and the reference lists were searched to identify articles related to Paxlovid-induced tacrolimus toxicity, using keywords, like drug interactions, Paxlovid, ritonavir, nirmatrelvir, tacrolimus, pharmacokinetic interactions, and CYP3A.ResultsTacrolimus is a substrate of CYP3A enzymes and ritonavir of Paxlovid has been identified as a potent inhibitor of CYP3A enzymes. Hence, Paxlovid can inhibit the CYP3A-mediated metabolism of tacrolimus, resulting in elevated plasma concentrations of tacrolimus and toxicity.ConclusionA number of case reports and case series have been published to highlight the association of Paxlovid and tacrolimus toxicity in transplant recipients with COVID-19 infection. Various recommendations have been proposed to prevent and mitigate the adverse events related to the DDI of Paxlovid and tacrolimus. Transplant physicians should be aware of this DDI and collaborate with clinical pharmacists on this issue.
Keywords: CYP3A